Improving Short Passing Stopping Skills Through The Diamond Passing Training Method An Experimental Study on 10-11 Year Old Soccer Players - Angga Pramudia; Nina Sutresna; Mochamad Yamin Saputra (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to examine the effect of diamond passing drills on improving short passing and stopping skills in 10-11 year old soccer players. Short passing and stopping techniques are very important in maintaining smooth gameplay and effective team strategy. The study used an experimental method with a one-group pre-test and post-test design involving 20 students from SSB Roksi as samples. The treatment, which consisted of diamond passing training, was given for four weeks with a frequency of three times per week. Skill data were measured before and after the treatment using a standardized instrument. Data analysis included the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test. The results of the analysis showed an increase in the average score for short passing stopping skills from 9.25 in the pre-test to 15.10 in the post-test. The t-test showed a significance value of p = 0.000 (p < 0.05), which means that there was a significant improvement in ability after diamond passing training. The conclusion of the study states that the diamond passing training method is effective in improving short passing stopping skills in young athletes. This study recommends that coaches implement this method in basic soccer technique training programs for 10-11 year olds.